Chromatin Landscape During Skeletal Muscle Differentiation - Hernández-Hernández, Oscar; Ávila-Avilés, Rodolfo Daniel; Hernández-Hernández, J. Manuel (Frontiers in Genetics, 2020)
Cellular commitment and differentiation involve highly coordinated mechanisms by which tissue-specific genes are activated while others are repressed. These mechanisms rely on the activity of specific transcription factors, chromatin remodeling enzymes, and higher-order chromatin organization in order to modulate transcriptional regulation on multiple cellular contexts. Tissue-specific transcription factors are key mediators of cell fate specification with the ability to reprogram cell types into different lineages. A classic example of a master transcription factor is the muscle specific factor MyoD, which belongs to the family of myogenic regulatory factors (MRFs). MRFs regulate cell fate determination and terminal differentiation of the myogenic precursors in a multistep process that eventually culminate with formation of muscle fibers. This developmental progression involves the activation and proliferation of muscle stem cells, commitment, and cell cycle exit and fusion of mononucleated myoblast to generate myotubes and myofibers. Although the epigenetics of muscle regeneration has been extensively addressed and discussed over the recent years, the influence of higher-order chromatin organization in skeletal muscle regeneration is still a field of development. In this review, we will focus on the epigenetic mechanisms modulating muscle gene expression and on the incipient work that addresses three-dimensional genome architecture and its influence in cell fate determination and differentiation to achieve skeletal myogenesis. We will visit known alterations of genome organization mediated by chromosomal fusions giving rise to novel regulatory landscapes, enhancing oncogenic activation in muscle, such as alveolar rhabdomyosarcomas (ARMS).